EXPERIMENTAL STUDY OF FORMATION 7TH GRADE STUDENTS HAVE SELF-CONTROL SKILLS (Pedagogy of Higher and Secondary Education, 2022)
Irina Seregina’s article “The forming of skills of self-control of students of the 7th grade ” deals with the problem of forming skills of self-control of the students of basic school during the studying process. Experimental research o f the development of self-control of the students of the 7th grade was made at the Russian Language lessons.